Pediatric cardiovascular care in Uganda: Current status, challenges, and opportunities for the future - Twalib Olega Aliku; Sulaiman Lubega; Judith Namuyonga; Tom Mwambu; Michael Oketcho; John O Omagino; Craig Sable; Peter Lwabi (Wolters Kluwer Medknow Publications, 2017)
In many developing countries, concerted action against common childhood infectious diseases has resulted in remarkable reduction in infant and under-five mortality. As a result, pediatric cardiovascular diseases are emerging as a major contributor to childhood morbidity and mortality. Pediatric cardiac surgery and cardiac catheterization interventions are available in only a few of Sub-Saharan African countries. In Uganda, open heart surgeries (OHSs) and interventional procedures for pediatric cardiovascular disease are only possible at the Uganda Heart Institute (UHI), having been started with the help of expatriate teams from the years 2007 and 2012, respectively. Thereafter, independent OHS and cardiac catheterization have been possible by the local team at the UHI since the year 2009 and 2013, respectively. The number of OHSs independently performed by the UHI team has progressively increased from 10 in 2010 to 35 in 2015, with mortality rates ranging from 0% to 4.1% over the years. The UHI pediatric catheterization team has independently performed an increasing number of procedures each year from 3 in 2013 to 55 in 2015. We herein describe the evolution and current status of pediatric cardiovascular care in Uganda, highlighting the unique aspects of its establishment, existing constraints, and future plans.